Initial results from the off‐label use of the SAPIEN S3 valve for percutaneous transcatheter pulmonary valve replacement: A multi‐institutional experience. Issue 3 (7th December 2018) - Sinha, Sanjay; Aboulhosn, Jamil; Asnes, Jeremy; Bocks, Martin; Zahn, Evan; Goldstein, Bryan H.; Zampi, Jeffrey; Hellenbrand, William; Salem, Morris; Levi, Daniel
Abstract: Objectives: To describe a multi‐center experience of percutaneous transcatheter pulmonary valve replacement (TPVR) using the Edwards Sapien S3 Valve. Background: Off‐label use of the Sapien S3 valve can allow for TPVR in patients with congenital heart disease (CHD) and large diameter dysfunctional right ventricular outflow tract (RVOT). The initial experience at five centers with the SAPIEN S3 valve for TPVR is presented with a focus on procedural techniques, success, complications, and efficacy. Methods: A retrospective review was performed of all patients with CHD and dysfunctional RVOT who underwent TPVR using Sapien S3 valve. Imaging data, procedural elements, and clinical follow‐up data were collected to evaluate acute and short‐term results. Results: A total of 50 patients underwent percutaneous placement of the Sapien S3 in the pulmonary position. Of these, 38 were placed into "native RVOTs", measuring 24–32 mm in diameter, as assessed by compliant balloon sizing. In all cases, the valve was implanted after introduction and there were no cases of valve embolization. On follow up (range 1–9 months, median 3 months), no patients had significant obstruction or regurgitation through or around the valve requiring intervention. There were no procedural deaths. Major complications included severe aortic compression (n = 1) and tricuspid valve (TV) injury related to valve placement (n = 2) and prestenting (n = 1). Conclusions: TPVR in patients with large diameter dysfunctional RVOTs can be effectively performed with the Sapien S3. All procedures were technically successful with no embolizations, no perivalvular leaks, and excellent short‐term valve function. Tricuspid valve injury from implantation of an uncovered valve was a serious procedural complication.